Selective Addition of Carbamoylsilane to Vicinal Diketones: Highly Efficient Synthesis of β-Keto-α-hydroxyamides - Cao, Pei; Wen, Xueping; Chen, Jianxin (Synlett, 2017)
The selective addition of carbamoylsilane to vicinal diketones in toluene solvent at 110 °C affords β-keto-α-siloxyamide derivatives in good yields (54–99%). The steric hindrance is an important factor in the addition reaction.
Keywords: diketones; carbamoylsilane; amides; addition; synthetic methods